Impact of Leadership Styles on Employees' Performance - Setiawan, I Gede Andri; nurtrisnawati; Sheidu, Comfort Fatimoh (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2024)
Purpose – This research is to determine the effect of leadership on employee performance. Methodology – This research uses qualitative methods and a literature review (Library Research) using an inductive analysis model. Researchers take library sources through online media on the Google Scholar application with the keyword "The influence of leadership on employee performance" with the publishing category since 2023 and based on the order of the date, the results obtained were still very large so a screening was carried out according to the objectives and relevance of the research, the results obtained were 8 articles for comparison. Findings and Discussion – The results of this study are that there is an influence of leadership on employee performance and there are other supporting factors that affect employee performance.